An alternative proposal for the reaction mechanism of light-dependent protochlorophyllide oxidoreductase - Silva, Pedro J. (2022)
Light-dependent protochlorophyllide oxidoreductase is one of the few known enzymes that require a quantum of light to start their catalytic cycle. Upon excitation, it uses NADPH to reduce the C17–C18 in its substrate (protochlorophyllide) through a complex mechanism that has heretofore eluded precise determination. Isotopic labeling experiments have shown that the hydride-transfer step is very fast, with a small barrier close to 9 kcal mol–1, and is followed by a proton-transfer step, which has been postulated to be the protonation of the product by the strictly conserved Tyr189 residue. Since the structure of the enzyme–substrate complex has not yet been experimentally determined, we first used modeling techniques to discover the actual substrate binding mode. Two possible binding modes were found, both yielding stable binding (as ascertained through molecular dynamics simulations) but only one of which placed the critical C17═C18 bond consistently close to the NADPH pro-S hydrogen and to Tyr189. This binding pose was then used as a starting point for the testing of previous mechanistic proposals using time-dependent density functional theory. The quantum-chemical computations clearly showed that such mechanisms have prohibitively high activation energies. Instead, these computations showed the feasibility of an alternative mechanism initiated by excited-state electron transfer from the key Tyr189 to the substrate. This mechanism appears to agree with the extant experimental data and reinterprets the final protonation step as a proton transfer to the active site itself rather than to the product, aiming at regenerating it for another round of catalysis.